Ensuring quality of life in palliative care physiotherapy in developing countries - Ogundunmade, Babatunde Gbolahan; John, Davidson Okwudili; Chigbo, Nnenna Nina (Frontiers in Rehabilitation Sciences, 2024)
Palliative care (PC) focuses on the body, mind, and spirit and can also provide pain and symptom relief, clarifying and focusing the provision of care on the patient's desires and goals, and helping them understand their disease and its treatment plans. Although PC is widely recognized for its applicability near the end of life or during terminal illness, it is also applicable and beneficial for patients with diseases in their earlier stages. Near the end of life, palliative care often focuses on providing continual symptom management and supportive care. Although palliative care has been noted to improve some life expectancy, its primary aim is to improve quality of life via focusing on the comfort of the patient, maintaining dignity, reducing intensive care utilization, and avoidance of expensive hospitalizations. One major challenge to quality of life for patients in PC is the physical and functional decline that occurs with disease progression. These issues can be addressed by specialized PC physiotherapy. Uniform provision of high-quality PC services (and physiotherapy in palliative care) faces substantial challenges in resource-challenged settings, including low- and middle-income countries. When properly integrated into PC teams and adequately supported, physiotherapy within PC can address common symptoms (pain, breathlessness, weakness) and assist patients to remain in an adapted home setting to optimize their quality of life, safety, and dignity.